Effect of head decapitation and planting density on quality seed production of sprouting broccoli (Brassica oleracea var. italica L.) (Journal of Applied and Natural Science, 2015)
A study was carried out to evaluate the effect of head decapitation and planting density on plant growth, seed yield and quality of sprouting broccoli, Brassica oleracea var. italica L. using cultivar ‘Green Head’. The twenty treatments comprised of combinations of four head decapitation methods viz., D1 (decapitation of primary head at appearance and harvesting seeds from secondary heads), D2 (decapitation of primary head at marketable stage and harvesting seeds from secondary heads), D3 (removal of secondary heads at appearance and harvesting seeds primary head) and ‘D4’ (No decapitation- control) and five planting densities viz., S1 (60x60 cm), S2 (60x45 cm), S3(45x45 cm), S4 (60x30 cm), and S5 (45x30 cm). Decapitation of primary head at appearance and harvesting seeds from secondary heads (D1) and planting density S3 (45x45 cm) independently as well as in combination gave highest seed yield per plot and per hectare. This combination was also found comparable to other combinations for other characters like days to 50% flowering, days to seed harvesting, plant height at harvesting (cm), number of branches per plant, number of siliqua per plant, siliqua length (cm), number of seeds per siliqua and seed quality parameters. Therefore, it is suggested that decapitation of primary head at appearance and harvesting seeds from secondary heads (D1) in combination with plant spacing of 45x45 cm i.e. D1S3 can be recommended for commercial seed production of sprouting broccoli.